Association of serum creatinine to cystatin C to waist circumference ratios and hypertension: evidence from China health and retirement longitudinal study - Yang, Yang; Sun, Qi; Ma, Shuang; Li, Xiaodan; Lang, Xinmiao; Zhang, Qi (Frontiers in Endocrinology, 2024)
The objective of this study was to explore the association between the ratio of serum creatinine to cystatin C to waist circumference (CCR/WC) and hypertension.The study utilized data extracted from the China Health and Retirement Longitudinal Study. In the cross-sectional analysis, logistic regression analyses were employed to examine the association between the CCR/WC ratio and hypertension. By utilizing restricted cubic splines, potential non-linear associations between the CCR/WC ratio and hypertension were explored. In the longitudinal analysis, the association between CCR/WC quartiles (Q1-Q4) and the risk of new-onset hypertension was evaluated by Cox proportional-hazards models. Results: In total, 7,253 participants were enrolled. The study unveiled an inverse association with hypertension, demonstrating an odds ratio (OR) of 0.29 (95% confidence interval [CI]: 0.23-0.37, P < 0.001). Among males, an OR of 0.38 (95% CI: 0.25-0.58, P < 0.001) was observed, while among females, an OR of 0.41 (95% CI: 0.28-0.60, P < 0.001) was noted. There was an absence of a nonlinear association between the CCR/WC ratio and hypertension. Cox regression analysis unveiled a reduced risk of hypertension in Q3 (Hazard ratios [HR]: 0.69, 95% CI: 0.58-0.82, P < 0.001) and Q4: (HR: 0.70, 95% CI: 0.59-0.83, P < 0.001) in compared to the Q1 of the CCR/WC ratio, and sex-specific analysis yielded consistent results.This study emphasizes the potential association between an elevated CCR/WC ratio and a reduced risk of hypertension.